2009
DOI: 10.1089/fpd.2009.0268
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of High Hydrostatic Pressure and Natural Antimicrobials on Inactivation Kinetics ofBacillus cereusin a Liquid Whole Egg and Skim Milk Mixed Beverage

Abstract: An in-depth study was conducted in order to extend the storage life of a liquid whole egg-skim milk (LWE-SM) mixed beverage to enhance its safety and the safety of related beverages. Bacillus cereus vegetative cells (1 x 10(8) colony-forming units [CFU]/mL) were inoculated in LWE-SM beverages with or without natural antimicrobial supplements: flavonol rich-cocoa powder (cocoanOX 12%, CCX) (700 ppm), vanillin (700 ppm), anise (700 ppm), and cinnamon (700 ppm). B. cereus cells were maintained at 10 degrees C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Since egg yolk solutions are sensitive to thermal treatments, high pressure treatment is an approved and effective alternative to eliminate micro‐organisms in food products (Anton and other , ). To circumvent the limitation of conventional pasteurization, HHP has been applied as a nonthermal technique for egg pasteurization (Anton and others , ; Pina‐Pérez and others ; Monfort and others ). The application of N 2 gas at a pressure of 13.7 MPa and 35 °C for 2 h has also been studied; however, it was shown that the combined application of HHP and N 2 was not effective in killing bacteria added to egg yolk (Wei and others ).…”
Section: Challenges Of Using Hhp For Microbial Inactivation In Egg Prmentioning
confidence: 99%
See 3 more Smart Citations
“…Since egg yolk solutions are sensitive to thermal treatments, high pressure treatment is an approved and effective alternative to eliminate micro‐organisms in food products (Anton and other , ). To circumvent the limitation of conventional pasteurization, HHP has been applied as a nonthermal technique for egg pasteurization (Anton and others , ; Pina‐Pérez and others ; Monfort and others ). The application of N 2 gas at a pressure of 13.7 MPa and 35 °C for 2 h has also been studied; however, it was shown that the combined application of HHP and N 2 was not effective in killing bacteria added to egg yolk (Wei and others ).…”
Section: Challenges Of Using Hhp For Microbial Inactivation In Egg Prmentioning
confidence: 99%
“…It has been demonstrated that microbial growth can also be inhibited by adding plant‐based antimicrobial compounds (Pina‐Pérez and others ). The combined effects of antimicrobials and HHP treatments were investigated to assess the possibility of reducing the pressure or the amount of antimicrobial compounds required to inactivate microorganisms (Ross and others ).…”
Section: Challenges Of Using Hhp For Microbial Inactivation In Egg Prmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies of the combinations of HP treatment with an antimicrobial addition for food safety have been reported in rice pudding, cooked chicken, beverages, and fermented sausages (Corbo et al 2009;Pina-Pérez et al 2009;Ananou et al 2010;Patterson et al 2011;Pulido et al 2012). Pina-Pérez et al (2011) researched HP treatment with the addition of various antimicrobials in beverages, and they reported that additive or synergistic effects were observed depending on the antimicrobial.…”
Section: Introductionmentioning
confidence: 99%